Decision analysis of slope ecological restoration based on AHP - Bai, Jianguang; Wang, Jianjun; Zhang, Yule; Ji, Xiaodong; Wen, Nan (Penerbit Universiti Kebangsaan Malaysia, 2017)
The serious deterioration of the ecological environment comes from a large number of geological disasters. These disasters were caused by a number of engineering activities. Ecological restoration is an important measure to reduce geological disasters and protect the ecological environment. On the basis of the introduction of cast-in-situ grids technology, external-soil spray seeding technology and vegetation bag technology, according to the ecological restoration experiment of the road slope attach to the Three Gorges Pumped-Storage Power Station in Hohhot, decision analysis of slope ecological restoration is done with AHP. It is shown that in arid and semi-arid area, selection of slope ecological restoration scheme mainly needs considering the ecological effect and stability. The major factor of ecological effects is survival rate of vegetation. The major factor of stability is the stability in a whole. Cast-in-situ grids technology will be the first choice for ecological restoration of road slope in arid and semi-arid area. This study provides reference for decision of the slope ecological restoration in arid and semi-arid region.